A comparison of radio-frequency biomotion sensors and actigraphy versus polysomnography for the assessment of sleep in normal subjects - O’Hare, Emer; Flanagan, David; Penzel, Thomas; Garcia, Carmen; Frohberg, Daniela; Heneghan, Conor (Sleep & breathing, 2015)
Purpose This paper aims to compare the absolute performance of three noncontact sleep measurement devices for measuring sleep parameters in normal subjects against polysomnography and to assess their relative performance. Methods The devices investigated were two noncontact radio-frequency biomotion sensors (SleepMinder (SM) and SleepDesign (HSL-101)) and an actigraphy-based system (Actiwatch). Overnight polysomnography measurements were carried out in 20 normal subjects, with simultaneous assessment of sleep parameters using the three devices. The parameters measured included total sleep time (TST), sleep efficiency (SE), sleep-onset latency (SOL), and wake-after-sleep onset (WASO). The per-epoch agreement level for sleep/wake distinction was evaluated. Results The TSTs reported by the three devices were 426 ± 34, 434 ± 22, and 441 ± 16 min, for the SM, HSL-101, and Actiwatch, respectively, against polysomnogram (PSG)-reported TST of 391 ± 49 min. The SOLs were 10 ± 10, 5 ± 6, and 3 ± 2 min for the SM, HSL-101 and Actiwatch, respectively against PSG SOL of 19 ± 13 min. The WASO times were 46 ± 33, 43 ± 22, and 38 ± 17 min, as against PSG-reported 69 ± 46 min. All three devices had a statistically significant bias to overestimate sleep time and underestimate WASO and SOL compared with PSG. The performance of the three devices was basically equivalent, with only minor interdevice differences. The overall per-epoch agreement levels were 86 % for the SM, 86 % for the HSL-101, and 85 % for the Actiwatch. Conclusions Noncontact biomotion approaches to sleep measurement provided reasonable estimates of TST, but with a bias to over-estimation of sleep. The radio-frequency biomotion sensors provided similar accuracies for sleep/wake determination in normal subjects as the actigraph used in this study and slightly improved estimates of TST, SOL, and WASO.